SIMULASI ANTENA DIPOLE ½ λ DENGAN FREKUENSI KERJA 128,4 MHz UNTUK RADIO PEMANCAR ATIS MENGGUNAKAN SOFTWARE SIMULASI DI BANDAR UDARA INTERNASIONAL HUSEIN SASTRANEGARA BANDUNG - ade irfansyah; sudrajat sudrajat; lailatul fitriyah (Jurnal Penelitian)
VHF telecommunications radio equipment, especially ATIS equipment is equipment used to inform information around the airport, such as weather, taxiways, runaway, etc. ATIS equipment works on frequencies between 118-137 MHz. The problem that arises is in the ATIS equipment that is the lack of antenna beam coverage on the ATIS radio transmitter, which is <100 NM, while the normal ATIS beam range is in the range of 150-200 NM. The author simulates dipole antenna ½ λ using the CST studio SUITE software application and compares the results of the simulation with the antenna specifications on the current ATIS equipment. Antenna simulation is done by making antenna dimensions and calculating the wavelength parameters, antenna length, antenna gap width, then the simulation results with the antenna length of 1040 mm and a gap of 5.545 mm, and a diameter of 3 mm, the results obtained are VSWR of 1.51 and return loss of -13,804, with a bandwidth of 12.13 MHz. These parameters were compared with the ATIS equipment antenna specifications at Bandung Husein Sastranegara International Airport and there was an increase in parameters after simulating.